PELATIHAN PUBLIKASI DI JURNAL ILMIAH BAGI GURU SD N JAMBUGEULIS - Adi, Yogi Kuncoro; Arifin, Slamet; Wulandari, Isnaini (Universitas Djuanda, 2024)
Low publication from classroom action research report was a problem in Jambugeulis Elementary School. Therefore, scientific publication training was needed to improve the teachers' knowledge and skills about the strategy and processes to publish in scientific journals. The implementing method of community service activities through lecturing, discuss, question and ask, and practice. This activity was followed by 10 elementary school teachers at Jambugeulis Elementary School in three days. The training material was focused on the new orientation of scientific publications, characteristic of scientific journals, manuscripts preparation, publication processing, ethics, and plagiarism. After training, the teacher's knowledge and skills improvement were seen based on his and her enthusiasm during the discussion and practice activities. In the future activity, the assistance is needed in publication until his and her manuscript is received in scientific journals. Keywords: classroom action research, scientific publication, training